Criminal Liability for Sexual Intercourse Against Children: Victim Protection and the Application of Restorative Justice in Indonesian Criminal Law - Monicha Dwi Yudiawati; Yogi Prasetyo; Sugeng Wibowo (Faculty of Law, Universitas Lampung, 2025)
Sexual intercourse with children is a criminal offense that causes long-term physical, psychological, and social harm. The dominance of retributive sentencing raises concerns about the marginalization of victim recovery and restorative justice. This study examines whether Indonesian criminal law, in practice, has integrated victim-oriented protection and restorative principles in adjudicating sexual offenses against minors. Using normative legal research with a case approach, it analyzes statutory child protection provisions and the ratio decidendi of Ponorogo District Court Decision Number 16/PID.SUS/2025/PN Png, focusing on the construction of fault (schuld), judicial reasoning, and sentencing orientation, particularly regarding juvenile consent and restorative justice. The findings show that the court strictly applied Article 81 paragraph (2) of the Child Protection Law, affirming the legal irrelevance of a child’s consent and recognizing persuasion through promises of marriage as sufficient to establish intent (dolus). The defendant was sentenced to eight years’ imprisonment and a fine of IDR 200 million, reflecting a predominantly retributive and deterrent approach. However, the judgment gave limited attention to restorative justice, as victim recovery, psychological rehabilitation, and participatory restorative measures were not explicitly incorporated into the sentencing rationale..